Preliminary Observations on the Exudation of Gum in Anogeissus latifolia Wall - Ghosh, S. S.; Purkayastha, S. K. (Indian Forester, 1959)
Anogeissus latifolia Wall. trees which yield "Ghatti Gum" of commerce do not normally possess gum canals either in the bark or in the wood. The gum that is exuded usually comes out from the gum pockets formed as a result of some injury in the bark. When the trees are heavily injured, gum canals are developed in the cambial zone and take part also in the exudation of gum. These canals though vertically aligned are not long as the effects of the wound are rather localized. The gum pockets and the gum canals are formed lysigenously by the dissolution of tissues. The injury also brings about certain other anatomical changes particularly in the region of the secondary phloem. The most notable changes are in the increase in the size and number of sclerosed cells which become very conspicuous in the bark. The traumatic gum canals in the wood are also characteristic due to their shape, size and arrangement.